Determinant Factors of Regional Inflation in Decentralized Indonesia - Brodjonegoro, Bambang P. S.; Simorangkir, Iskandar; Gitaharie, Beta Y.; Falianty, Telissa (Economics and Finance in Indonesia, 2005)
.